Rapidly directional biotransformation of tauroursodeoxycholic acid through engineered Escherichia coli. (1st July 2017) - Shi, Jie; Wang, Jie; Yu, Lu; Yang, Li; Zhao, Shujuan; Wang, Zhengtao
Abstract: Bear bile powder is a precious medicinal material. It is characterized by high content of tauroursodeoxycholic acid (TUDCA) at a ratio of 1.0–1.5 to taurochenodeoxycholic acid (TCDCA). Here, we reported the biotransformation of tauroursodeoxycholic acid (TUDCA) through Escherichia coli engineered with a two-step mimic biosynthetic pathway of TUDCA from taurochenodeoxycholic acid (TCDCA). Two 7α-hydroxysteroid dehydrogenase (7α-HSDH) and two 7β-hydroxysteroid dehydrogenase (7β-HSDH) genes (named as α1, α2, β1, and β2 ) were selected and synthesized to create four pathway variants using ePathBrick. All could convert TCDCA to TUDCA and the one harboring α1 and β2 (pα1 β2 ) showed the strongest capability. Utilizing the oxidative and reductive properties of 7α- and 7β-HSDH, an ideal balance between TUDCA and TCDCA was established by optimizing the fermentation conditions. By applying the optimal condition, E. coli containing pα1 β2 (BL-pα1 β2 ) produced up to 1.61 ± 0.13 g/L of TUDCA from 3.23 g/L of TCDCA at a ratio of 1.3 to TCDCA. This study provides a potential approach for bear bile substitute production from cheap and readily available chicken bile.